Pengaturan Hukum Pengamanan Aset Tanah Kas Desa Berdasarkan Peraturan Perundang-Undangan di Indonesia - Tomson Purba; Syamsir Syamsir (Universitas Batanghari Jambi, 2025)
As a source of income for the village, village treasury land does not yet have specific regulations governing its management and utilization. As a result, Village Treasury Land cannot be utilized professionally, thus hampering Village development. To determine and analyze the legal arrangements for securing village treasury land is the purpose of this study. This study uses normative legal research methods with legal materials from statutory, conceptual, and historical laws by applying inventory, systematization, and interpretation techniques. Because specific regulations regarding village treasury land are not found in laws or implementing regulations below or in regulations equivalent to implementing regulations, the results of this study can be used to create Village Regulations. Therefore, to obtain legal certainty, the Village Head has the authority to create Village Regulations in the Utilization and Management of Village Treasury Land.